Assessment of Steel Subjected to the Thermomechanical Control Process with Respect to Weldability - Jacek Górka (Metals, 2018)
The study is concerned with the assessment of the weldability of steel S700MC subjected to the thermomechanical control process (TMCP) and precipitation hardening and characterised by a high yield point. Appropriate mechanical and plastic properties of steel S700MC were obtained using the thermomechanical control process through precipitation, solution, and strain hardening as well as by using grain-refinement-related processes. Constituents responsible for the hardening of steel S700MC include Ti, Nb, N, and C. The hardening is primarily affected by (Ti,Nb)(C,N)-type dispersive precipitates sized from several nanometres to between ten and twenty nanometres. The welding process considerably differs from TMCP conditions, leading to the reduction of plastic properties both in the heat-affected zone (HAZ) and in the weld area. This study demonstrates that in cases of TMCP steels, where the effect of precipitation hardening is obtained through titanium and niobium hardening phases, the carbon equivalent and phase transformation γ–α cannot constitute the basis of weldability assessment. The properties of welded joints made from the above-named group of steels are primarily affected by the stability of hardening phases, changes in their dispersion, and ageing processes. The most inferior properties were identified in the high-temperature and coarse-grained HAZ area, where the nucleation of hardening phases in the matrix and their uncontrolled reprecipitation in the fine-dispersive form lead to a sharp decrease in toughness.